Polymorphism Pro64His within galectin-3 has functional consequences at proteome level in thyroid cells - Silvestri, Roberto; Zallocco, Lorenzo; Corrado, Alda; Ronci, Maurizio; Aceto, Romina; Ricci, Benedetta; Cipollini, Monica; Dell’Anno, Irene; De Simone, Chiara; De Marco, Giuseppina; Ferrarini, Eleonora; Beghelli, Daniela; et al. (Frontiers in Genetics, 2024)
Introduction: The single nucleotide polymorphism (SNP) rs4644 at codon 64 of galectin-3 (gal-3, gene name: LGALS3), specifying the variant proline (P64) to histidine (H64), is known to affect the protein’s functions and has been associated with the risk of several types of cancer, including differentiated thyroid carcinoma (DTC). Materials and methods: To deepen our understanding of the biological effects of this SNP, we analyzed the proteome of two isogenic cell lines (NC-P64 vs NA-H64) derived from the immortalized non-malignant thyrocyte cell line Nthy-Ori, generated through the CRISPR-Cas9 technique to differ by rs4644 genotype. We compared the proteome of these cells to detect differentially expressed proteins and studied their proteome in relation to their transcriptome. Results: Firstly, we found, consistently with previous studies, that gal-3-H64 could be detected as a monomer, homodimer, and heterodimer composed of one cleaved and one uncleaved monomer, whereas gal-3-P64 could be found only as a monomer or uncleaved homodimer. Moreover, results indicate that rs4644 influences the expression of several proteins, predominantly upregulated in NA-H64 cells. Overall, the differential protein expression could be attributed to the altered mRNA expression, suggesting that rs4644 shapes the function of gal-3 as a transcriptional co-regulator. However, this SNP also appeared to affect post-transcriptional regulatory mechanisms for proteins whose expression was oppositely regulated compared to mRNA expression. It is conceivable that the rs4644-dependent activities of gal-3 could be ascribed to the different modalities of self-dimerization. Conclusion: Our study provided further evidence that rs4644 could affect the gal-3 functions through several routes, which could be at the base of differential susceptibility to diseases, as reported in case-control association studies.